Does training increase outflows from unemployment: evidence from Latvian regions - Jekaterina Dmitrijeva; Mihails Hazans (European Regional Science Association (ERSA), 2004)
Monthly panel (1998-2003) data from regional labor offices in Latvia are used to conclude on the specificity of matching process in this transition economy and to evaluate the impact of active labor market policy programs on outflows from unemployment. Results confirm that the hiring process is driven by stock-flow matching rather than by traditional matching function: stock of unemployed at the beginning of the month and vacancies arriving during the month are the key determinants of outflow from unemployment to employment, while stock of vacancies and inflow of unemployed are not significant. In the context of such “correct” specification of the matching process, the policy evaluation is performed. We find positive and very significant effect of training on outflows from unemployment to employment, thus providing some evidence against cuts in training expenditures. Fixed effects estimates allow discriminating between regions in terms of matching efficiency. JEL: J41, J64, J68 Keywords: stock-flow matching, augmented matching function, labour market policy, training
Keywords: J41; J64; J68; 330; stock-flow matching; augmented matching function; labour market policy; training